In utero protein restriction causes growth delay and alters sperm parameters in adult male rats - Toledo, Fabiola C. [UNESP]; Perobelli, Juliana E. [UNESP]; Pedrosa, Flavia P. C. [UNESP]; Anselmo-Franci, Janete A.; Kempinas, Wilma D. G. [UNESP] (Biomed Central Ltd., 2011)
Background: Recent studies have supported the concept of fetal programming which suggests that during the intrauterine development the fetus may be programmed to develop diseases in adulthood. The possible effects of in utero protein restriction on sexual development of rat male offspring were evaluated in the present study.Methods: Pregnant Wistar rats were divided into two experimental groups: one group treated with standard chow (SC, n = 8, 17% protein) and the other group treated with hypoproteic chow (HC, n = 10, 6% protein) throughout gestation. After gestation the two experimental groups received standard chow. To evaluate the possible late reproductive effects of in utero protein restriction, the male offspring of both groups were assessed at different phases of sexual development: prepubertal (30 days old); peripubertal (60 days old); adult (90 days old). Student's t test and Mann-Whitney test were utilized. Differences were considered significant when p < 0.05.Results: We found that in utero protein restriction reduced the body weight of male pups on the first postnatal day and during the different sexual development phases (prepubertal, peripubertal and adult). During adulthood, Sertoli cell number, sperm motility and sperm counts in the testis and epididymal cauda were also reduced in HC. Furthermore, the numbers of sperm presenting morphological abnormalities and cytoplasmic drop retention were higher in HC.Conclusions: In conclusion, in utero protein restriction, under these experimental conditions, causes growth delay and alters male reproductive-system programming in rats, suggesting impairment of sperm quality in adulthood.